The Effectiveness of Progressive Muscle Relaxation on the Postpartum Quality of Life: A Randomized Controlled Trial - İlknur Gökşin; Sultan Ayaz-Alkaya (Elsevier, 2018)
Purpose: This study aimed to determine the effectiveness of progressive muscle relaxation (PMR) on the quality of life of women during postpartum period. Methods: A randomized controlled trial design was used. The participants consisted of primiparous women who had experienced a vaginal birth in the obstetrics department of a hospital. Thirty women in the intervention group and 30 women in the control group were included. Data were collected using the Maternal Postpartum Quality of Life Questionnaire (MAPP-QoL) between June 2016 and April 2017. PMR was applied to the intervention group. PMR was performed as contracting a muscle group and then relaxing it, moving (or progressing) from one muscle group to another. Results: The mean pretest and posttest scores of the MAPP-QoL in the intervention group were 24.43 ± 4.58 and 26.07 ± 4.58, respectively (t = −2.73, p < .05). The mean pretest and posttest scores of the MAPP-QoL in the control group were 23.29 ± 4.37 and 21.99 ± 5.58, respectively (t = 2.23, p < .05). The difference between the mean scores of the women in the intervention and control groups before PMR was not statistically significant (t = 0.99, p > .05), whereas the difference between the groups after PMR was found to be statistically significant (t = 3.09, p < .05). Conclusion: Postpartum quality of life of women was increased after PMR. It is recommended that PMR be taught to women who are admitted to obstetrics and outpatient clinics and home visits be completed to expand the use of PMR. Keywords: muscle relaxation, postpartum period, quality of life, woman